A Study to Ascertain the Expression of Aquaporin 4 and Neuropeptide Y in the Jejunal Mucosa Secondary to Traumatic Brain Injury in Humans - Patil, Parag Parshuram; Subramanian, Arulselvi; Aggarwal, Garima; Lalwani, Sanjeev; Agrawal, Deepak (Indian Journal of Neurotrauma, 2020)
Introduction Gastrointestinal (GI) dysfunction is a common complication in patients with traumatic brain injury (TBI). Studies in rats have shown alterations in intestinal mucosa to correlate with severity and duration of TBI. There is lack of such evidence in humans. So we intended to find correlation between histopathological changes and expression of aquaporin 4 (AQ4) and neuropeptide Y (NPY) in jejunal mucosa in post TBI patients.Materials and Methods Autopsy specimens of jejunum were obtained from patients who had died due to TBI (n = 20), patients dying due to traumatic injury other than TBI, and patients who were brought dead (diseased controls n = 20). Abdominal trauma was the exclusion criterion for both. Jejunal specimens were grossly examined and then analyzed histopathologically and graded immunohistochemically for AQ4 and NPY. Unpaired t-test was used to compare results.Results After exclusion, 19 cases and 17 controls were studied. No significant difference was observed in the microscopic findings between cases and controls (p-value = 0.70). The expression of AQ4 was more in cases (p-value = 0.04). NPY expression was not significantly different (p-value = 0.93).Conclusion AQ4 can hence be used as a marker of GI injury post TBI. Histopathological examination cannot distinguish between these changes.
Keywords: traumatic brain injury; aquaporin 4; neuropeptide Y